2018
DOI: 10.1164/rccm.201706-1301oc
|View full text |Cite
|
Sign up to set email alerts
|

Nintedanib with Add-on Pirfenidone in Idiopathic Pulmonary Fibrosis. Results of the INJOURNEY Trial

Abstract: Nintedanib with add-on pirfenidone had a manageable safety and tolerability profile in patients with IPF, in line with the adverse event profiles of each drug. These data support further research into combination regimens in the treatment of IPF. Clinical trial registered with www.clinicaltrials.gov (NCT02579603).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
155
2
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 225 publications
(176 citation statements)
references
References 11 publications
11
155
2
8
Order By: Relevance
“…Overall, our observations support the inclusion of patients with more advanced lung function impairment in future IPF trials investigating novel therapies, as well as combination antifibrotic therapy [28,29]. Whether patients with even greater lung function impairment than those included in this analysis should be included in future clinical trials is open to speculation, but it is certainly a concept for further investigation.…”
Section: Discussionsupporting
confidence: 63%
“…Overall, our observations support the inclusion of patients with more advanced lung function impairment in future IPF trials investigating novel therapies, as well as combination antifibrotic therapy [28,29]. Whether patients with even greater lung function impairment than those included in this analysis should be included in future clinical trials is open to speculation, but it is certainly a concept for further investigation.…”
Section: Discussionsupporting
confidence: 63%
“…It is generally recognized that alveolar epithelial cell injury and inflammation lead to aberrant proliferation of fibroblasts, resulting in an exaggerated deposition of extracellular matrix (ECM) in the lung parenchyma and eventually leading to lung function damage (2). However, the molecular mechanism underlying IPF is not fully understood, and there is still lack of effective treatment for IPF aside from lung transplantation, even though a number of studies have reported the anti-fibrotic effects of nintedanib and pirfenidone on lung fibrosis (3)(4)(5). Therefore, it is of great value to reveal the pathogenesis of IPF and to explore more effective therapeutic strategies and drugs for the treatment of IPF.…”
mentioning
confidence: 99%
“…Additionally, they note that, due to the similar adverse event profile of the two therapies, there was uncertainty in identifying the treatment responsible for some of the TEAEs. Vancheri et al 43 also reported on the safety of combination therapy, and found that gastrointestinal adverse events occurred in 69.8% of patients treated with nintedanib with add-on pirfenidone and 52.9% of patients treated with nintedanib. Crestani et al 44 examined the long-term safety of nintedanib.…”
Section: Discussionmentioning
confidence: 99%